Kesesuaiaan Praktik Akad Syariah pada Layanan Pembiayaan di Baitul Maal Wat Tamwil (BMT) UGT Nusantara Berdasarkan Fatwa DSN-MUI - Lilis Wike Wartina; Azwar Azwar; Nur Annisa; Ruwaida Sinaga; Arman Solo Harahap; Toni Pangidoan Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The development of Islamic financial institutions in Indonesia has encouraged the increasing use of sharia contracts in microfinance institutions, including Baitul Maal wat Tamwil (BMT). However, in practice, there are still inconsistencies between the implementation of contracts and the provisions of DSN-MUI Fatwas. This study aims to analyze the conformity of sharia contract practices in financing services at BMT UGT Nusantara based on DSN-MUI Fatwas. This research used a descriptive qualitative approach with a field research method. Data were collected through interviews and documentation related to financing products and the contracts applied. The results showed that BMT UGT Nusantara implements various sharia contracts, including mudharabah, musyarakah, murabahah, ijarah, kafalah, wakalah, and qard al-hasan. In general, the implementation of these contracts has complied with DSN-MUI Fatwas, particularly in terms of margin transparency, ownership of goods before the contract, and the application of reasonable ujrah. However, several aspects still need improvement, especially in the implementation of murabahah bil wakalah and the limited administrative capabilities of members, which cause profit-sharing contracts to be rarely applied. This study concludes that the level of sharia compliance at BMT UGT Nusantara is influenced by the institution’s commitment and the members’ capacity in business and financial management.